IL-1β activates p44/42 and p38 mitogen-activated protein kinases via different pathways in cat esophageal smooth muscle cells - Lee, Tai Sang (Baishideng Publishing Group Co., Limited, 2006)
AIM: To examine the pathway related to the IL-1β-induced activation of mitogen-activated protein (MAP) kinases in cat esophageal smooth muscle cells. METHODS: Culture of the esophageal smooth muscle cells from cat was prepared. Specific inhibitors were treated before applying the IL-1β. Western blot analysis was performed to detect the expressions of COX, iNOS and MAP kinases. RESULTS: In the primary cultured cells, although IL-1β failed to upregulate the COX and iNOS levels, the levels of the phosphorylated forms of p44/42 MAP kinase and p38 MAP kinase increased in both concentration- and time-dependent manner, of which the level of activation reached a maximum within 3 and 18 h, respectively. The pertussis toxin reduced the level of p44/42 MAP kinase phosphorylation. Tyrphostin 51 and genistein also inhibited this activation. Neomycin decreased the density of the p44/42 MAP kinase band to the basal level. Phosphokinase C (PKC) was found to play a mediating role in the IL-1β-induced p44/42 MAP kinase activity. In contrast, the activation of p38 MAP kinase was inhibited only by a pretreatment with forskolin, and was unaffected by the other compounds. CONCLUSION: Based on these results, IL-1β-induced p44/42 MAP kinase activation is mediated by the Gi protein, tyrosine kinase, phospholipase C (PLC) and PKC. The pathway for p38 MAP kinase phosphorylation is different from that of p44/42 MAP kinase, suggesting that it plays a different role in the cellular response to IL-1β.